Antecollis and Parkinsonism in Adults with Dravet Syndrome - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Toronto Western and The Hospital for Sick Children, Toronto, Canada, prospectively studied the motor abnormalities in a consecutive sample of adults with genetically proven Dravet syndrome (DS).